Flavonoid compounds from Passiflora foetida L. collected in Thua Thien Hue - Phan, Thị Diễm Trân; Trần , Phương Hà; Tôn, Thất Hữu Đạt; Cường, Lê Cảnh Việt (Hue University Journal of Science: Natural Science, 2026)
Five flavonoid compounds: vitexin, vitexin 2ʹʹ-O-β-D-glucopyranoside, 2ʺ-O-rhamnosylvitexin, luteolin, and quercetin (1–5) were isolated from the leaves and stems of Passiflora foetida L. growing in Thua Thien Hue Province. Their chemical structures were elucidated by using nuclear magnetic resonance spectra as well as by comparing with the reported spectroscopic data. All the isolated compounds exhibited inhibitory activity against α-amylase and α-glucosidase enzymes with IC50 values ​​ranging from 123.6–743.4 µg/mL and 166.3–423.4 µg/mL, respectively. The results show the potential application of P. foetida in developing products to support diabetes treatment.